(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Near-peer assisted learning is well documented in literature. Peers have experience of going through a similar situation in the proximate past and have advantage of better conceptualization of basic concepts. This study aims to explore the experience of near-peer student tutors on learning as a consequence of their teaching, and to find out perceptions of staff tutors and tutees on perception of improvement, professionally. Subjects and Methods: It was a qualitative study based on interviews carried out in Ameer ud Din Medical College/ PGMI/ Lahore General Hospital, Lahore from January 2017 to June 2017. This study was designed using semi-structured in-depth interviews to collect data from Postgraduate Students Post-IMM (N=5) as student tutors, Pre-IMM students (N=2), final year medical students (N=2), fourth year medical students (N=2) as tutees and faculty members (N=2) as faculty staff tutors, selected on the basis of non-probability purposive sampling. The qualitative data was generated in interviews conducted in English, transcribed and organized into categories by using n-vivo. Participants were interviewed one more time to further explore their perceptions and experiences related to emergent categories. Grounded theory analysis technique was employed to generate qualitative data. It was then analyzed on n-vivo. Results: Near-Peer Assisted Learning (NPAL) was perceived as rewarding in terms of promoting higher order thinking, improving teaching skills and in refining self-efficacy among tutors. Both student tutors and tutees learnt with the interaction in this way. Conclusion: It was perceived that near-peer assisted learning had improvement in transfer of learning, when opportunities were provided through near-peer student tutors. Near-peer tutors, tutees and faculty staff tutors had similar perception, as it increased depth of their knowledge and skills.